Economic Analysis of Heritage Tourism at Old Town Area Surabaya - Muryani, Muryani (Journal of Developing Economies, 2019)
This study is an application of cultural heritage valuation using non-market methods. Contingent Valuation Method used to measure the amount of economic value by estimating willingness to pay from Surabaya residents. The economic value of the Old Town Area of Surabaya if there were improvementanddevelopment of heritage tourism is Rp. 1.471.764 billion.This value is greater than before improvement and development that is only Rp. 3.914.892.240. Multinomial logit regression was used to identify factors that affect the interest to visit and willingness to pay for the respondent. Results indicates that age, education, income, and knowledge significantly influence the interest to visit and willingness to pay. Therefore, it is necessary to encourage the development of heritage tourism, having regard to the determination of stakeholder and policy priorities.The method used in the determination of stakeholder and policy priorities is the Analytic Hierarchy Process.Overall, the use of three methods provide complete results so it can be a reference in the field of cultural heritage research and advice in the development of heritage tourism, especially in the old city area of Surabaya. Keywords: Economic Valuation, Multinomial Logistic Regression, Contingent Valuation Method, Analytical Hierarchy Process. JEL Classification: A130, D10